2017
DOI: 10.1016/j.jeem.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Self-enforcing environmental agreements and trade in fossil energy deposits

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The intersection of climate policy and fossil fuel production is also the subject of a growing body of research (Harstad 2012;Asheim 2012;Hoel 2013;Collier and Venables 2014;Lazarus et al 2015;Gerarden et al 2016;Muttitt et al 2016;Faehn et al 2017;Day and Day 2017;Eichner and Pethig 2017). Studies have examined, for example, the extent to which achieving climate protection objectives would dramatically curtail fossil fuel profits, or Brents^ (Bauer et al 2013), and render a significant fraction of coal and unconventional oil reserves and resources Bunburnable^(McGlade and Ekins 2015; Bauer et al 2015).…”
mentioning
confidence: 99%
“…The intersection of climate policy and fossil fuel production is also the subject of a growing body of research (Harstad 2012;Asheim 2012;Hoel 2013;Collier and Venables 2014;Lazarus et al 2015;Gerarden et al 2016;Muttitt et al 2016;Faehn et al 2017;Day and Day 2017;Eichner and Pethig 2017). Studies have examined, for example, the extent to which achieving climate protection objectives would dramatically curtail fossil fuel profits, or Brents^ (Bauer et al 2013), and render a significant fraction of coal and unconventional oil reserves and resources Bunburnable^(McGlade and Ekins 2015; Bauer et al 2015).…”
mentioning
confidence: 99%
“…The green paradox is the observation first made by Sinn (2008Sinn ( , 2012Sinn ( and 2015 that the owners of polluting assets (such as fossil fuels), when anticipating tightening of environmental policies, would accelerate extraction and consumption of fossil fuels for fear of their becoming worthless (stranded), hence accelerating global warming. Papers like Asheim 2012;Lazarus et al 2015;Gerarden et al2016;Muttitt et al 2016;Richter et al 2018;Collier and Venables 2014;Faehn et al 2017;Day and Day 2017;Eichner and Pethig 2017, Lazarus and van Asselt 2018, or Piggot et al, 2018 explore different variations of coal production taxes or output quotas that coal producers could initiate to ensure that as demand for coal drops their revenues do not fall correspondingly, thus relieving the pressure to accelerate fuel consumption and reversing the green paradox. Most recently Asheim et al (2019) called for a supply-side climate treaty, based on coordinated agreement to limit global fossil fuel supply by major producers.…”
Section: Background and The Problemmentioning
confidence: 99%
“…The implementation of this intention should include both reduction and balanced management of emissions. (Eichner and Pethig, 2017;Day and Day, 2017;Zeppini and van den Bergh, 2020). In the Regional Action Plan for Climate and Energy developed for the Małopolskie Voivodeship (Marshal's Office of the Małopolska Region, 2019), activities have been identified that will contribute to:…”
Section: Introductionmentioning
confidence: 99%